2021
DOI: 10.3389/fpsyg.2021.744201
|View full text |Cite
|
Sign up to set email alerts
|

Mattering Mediates Between Fairness and Well-being

Abstract: Research has suggested a fundamental connection between fairness and well-being at the individual, relational, and societal levels. Mattering is a multidimensional construct consisting of feeling valued by, and adding value to, self and others. Prior studies have attempted to connect mattering to both fairness and a variety of well-being outcomes. Based on these findings, we hypothesize that mattering acts as a mediator between fairness and well-being. This hypothesis was tested through Covariance-Based Struct… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
16
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
6
1

Relationship

3
4

Authors

Journals

citations
Cited by 17 publications
(21 citation statements)
references
References 125 publications
0
16
0
Order By: Relevance
“…Extensive evidence points to the fact that justice is a sine qua non condition for health and wellbeing [21,[26][27][28]. The text in the bottom row of Table 1 refers to the foundational definition of justice, which is to each according to his or her due.…”
Section: Justicementioning
confidence: 99%
See 1 more Smart Citation
“…Extensive evidence points to the fact that justice is a sine qua non condition for health and wellbeing [21,[26][27][28]. The text in the bottom row of Table 1 refers to the foundational definition of justice, which is to each according to his or her due.…”
Section: Justicementioning
confidence: 99%
“…According to Prilleltensky [ 18 ], mattering is based on the need ‘to feel valued by, and to add value to, self, others, work and community’ (p.16). As empirical studies have demonstrated [ 27 , 28 ], mattering mediates between experiences of justice and health. We hypothesize that this is the case because when people are treated fairly, they are treated with dignity and respect, made to feel valued and given chances to add value.…”
Section: Components Of the Public Goodmentioning
confidence: 99%
“…Executives' innovative motivation determines the firm's creative activity intensity (Duan et al, 2021). In practical terms, executives' perceptions of compensation fairness can motivate them to use their management talents (Scarpa et al, 2021). Then they will generate a stronger innovation motivation in the firm's long-term interest.…”
Section: Theory and Hypotheses Executive Compensation Fairness And Ex...mentioning
confidence: 99%
“…Second, considerable work has shown that fairness is a precondition for wellness (Prilleltensky, 2012). Third, there is growing evidence at the personal level that mattering mediates between wellness and justice (Scarpa, Di Martino, et al, 2021). When we combine these bodies of knowledge, we conclude that autonomy and relatedness may very well mediate between fairness and wellness at the national level.…”
Section: Introductionmentioning
confidence: 99%
“…The second theory guiding our effort is the psychology of mattering. Recent theoretical and empirical work has shown that mattering consists of feeling valued and adding value (Prilleltensky & Prilleltensky, 2021; Scarpa, Di Martino, et al, 2021; Scarpa, Prilleltensky, et al, 2021). Part of adding value is autonomy, and part of feeling valued is relatedness.…”
Section: Introductionmentioning
confidence: 99%